Subjective wellbeing, religiosity, and voting intention: The case of Malaysia - Koay, Ying Yin (2023)
The decrease in happiness, rise in commit suicide rate, and the lack of official wellbeing indicators in Malaysia have inspired the first study objective – discovering the determinants of Malaysian subjective wellbeing (SWB) based on the cross-sectional data from the sixth wave World Values Survey (WVS) with a sample size of 1209 respondents. Using the ordered probit and probit modelling approaches, this study finds that Malaysians cares about safety and self-esteem needs in their pursuit of SWB. Hence, the government and policy makers may have the policies that can enhance Malaysian financial satisfaction (for safety needs) and respect to human rights (for self-esteem needs) in stimulating greater SWB. Additionally, religions are deemed as an aid mechanism in overcoming the challenges in life. With the multi-religious culture in Malaysia, this study also shows that religiosity helps to improve the happiness of B40 (the lowest income groups in the country and their welfares are always prioritized by the government due to their tight financial circumstances). Furthermore, the moderating role of religiosity in enhancing the SWB of being self-actualizing is also found in this study. Hence, parents may cultivate religious values among their children since young at home. The government may consider to nurture a religious society through education. The 12th General Election in Malaysia has a turnout rate which has not seen since 1964. This was also the year when digital media started penetrating political communication. Hence, the last objective of this study is to examine the impact of digital media and life satisfaction on Malaysians’ voting intention. Using the sixth wave WVS of 1198 respondents, the Hierarchical Linear Regression Modelling results show that life satisfaction and voting intention go in an opposite direction without digital media. Individuals who are not satisfied with life have greater intention to vote vis-à-vis those with greater life satisfaction. Hence, election outcome is more likely to reflect a proportional preference among voters with different life satisfactions. By democratizing access to information with the presence of digital media, voting intention is levelled irrespective of the degree of life satisfaction. Therefore, voters are encouraged to excess more information through digital media before an election. Gaining a better understanding of national affairs instead of overly focusing on personal life satisfaction helps to make a right voting decision if vote or not to vote.